Modeling the economic impact for Chile of an import ban on genetically modified maize - William Foster; Jorge Ortega; Gonzalo Vargas (GM Crops & Food)
We estimate producer and consumer surplus changes due to a possible GM maize import ban in Chile, which produces only non-GM grains for internal use. Without foreign non-GM sources, the ban’s effect on domestic maize prices would be so significant as to induce Chile to switch from net exporter to net importer of animal products. Fixed factor owners in farm production would benefit significantly, although non-GM maize imports would moderate gains. Total social welfare measures would decline considerably, requiring large offsetting noneconomic benefits for a ban’s political viability. Without non-GM imports, internal maize prices would likely eliminate domestic animal product industries; with possible imports, industries and final consumers would suffer, but much less. Currently, the country is a net importer of grain and a net exporter of pork and poultry, and so most welfare losses on the demand side of the market for maize would be in terms of the economic rents generated by the pork and poultry sectors. International competition would protect final consumers to the extent that animal product imports based on GM feed were permitted.